2016
DOI: 10.1093/scipol/scw016
|View full text |Cite
|
Sign up to set email alerts
|

Does it take two to tango? Factors related to the ease of societal uptake of scientific knowledge

Abstract: Science policy increasingly focuses on maximising societal benefits from science and technology investments, but often reduces those benefits to activities involving codifying and selling knowledge, thereby idealising best practice academic behaviours around entrepreneurial superstars. This paper argues that societal value depends on knowledge being used, making knowledge's eventual exploitation partly dependent upon on whether other users -societal or scientific -can use that knowledge, i.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
(30 reference statements)
1
3
0
Order By: Relevance
“…There are some parallels with the finding from a recent study looking to distil the factors that make researchers more likely to be open to including end-user's knowledge in their research processes (Olmos-Peñuela, Benneworth, & Castro-Martínez, 2016). This study found that personal characteristics do not affect the researchers' propensity to incorporate user knowledge, nor did different types of research fields (for example, those researchers in science fields compared to social science fields).…”
Section: The Importance Of Different Researcher Identitiessupporting
confidence: 53%
“…There are some parallels with the finding from a recent study looking to distil the factors that make researchers more likely to be open to including end-user's knowledge in their research processes (Olmos-Peñuela, Benneworth, & Castro-Martínez, 2016). This study found that personal characteristics do not affect the researchers' propensity to incorporate user knowledge, nor did different types of research fields (for example, those researchers in science fields compared to social science fields).…”
Section: The Importance Of Different Researcher Identitiessupporting
confidence: 53%
“…There are also significant interdependencies between practices that connect academic scientists to industry, implying that it does not make sense to champion one practice as inherently preferable. Boosting university-industry interaction requires a range of approaches that grow out of underlying personal ties (Feller and Feldman 2010;Olmos-Peñuela, Benneworth, and Castro-Martínez 2016;. For instance, commercialisation will often be an outcome of or a follow-on activity to collaboration between academic scientists and industry actors, rather than a stand-alone activity (e.g.…”
Section: Industry Actors As Co-creators In the Scientific Research Prmentioning
confidence: 99%
“…: Challenging disciplinary stereotypes of research's social value' (Olmos-Peñuela et al, 2014) and 'Does it take two to tango? Factors related to the ease of societal uptake of scientific knowledge' (Olmos-Peñuela et al, 2016).…”
Section: Paul Benneworthmentioning
confidence: 99%